2017
DOI: 10.1016/j.yexmp.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic analysis of oral cells in the high wavenumber region

Abstract: Raman spectroscopy can provide a molecular-level signature of the biochemical composition and structure of cells with submicrometer spatial resolution and could be useful to monitor changes in composition for early stage and non-invasive cancer diagnosis, both ex-vivo and in vivo. In particular, the fingerprint spectral region (400-1800cm) has been shown to be very promising for optical biopsy purposes. However, limitations for discrimination of dysplastic and inflammatory processes based on the fingerprint re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Subcellular DNA (Carvalho et al, 2017) and DNA information from dehydrated cells (Panikkanvalappil et al, 2013) also provide more valid information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcellular DNA (Carvalho et al, 2017) and DNA information from dehydrated cells (Panikkanvalappil et al, 2013) also provide more valid information.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding nuclear recognition, the specificity was 99%. Compared to other methods, highwavenumber regions provide more information about subcellular structures to distinguish between normal, premalignant, and malignant tissues (Carvalho et al, 2015;Carvalho et al, 2017).…”
Section: Diagnosis and Classification Of Oral Cancermentioning
confidence: 99%
“…Santos et al investigated the effects of different optical fibers on 720 nm laser based Raman spectroscopy and demonstrated the system was capable of acquireing HW Ramang signals from sliced porce brain tissues [28]. Carvalho et al demonstrated HW Raman signals may be obtained with 532 nm laser from oral cells immersed in distilled water [29]. Barroso et al studied the difference of HW Raman signals between healthy and cancer oral tissues and found that water contents may be used as a biomarker for cancer diagnosis [30].…”
Section: Hw Raman Analysis On Biological Tissues Using Ccd Detectorsmentioning
confidence: 99%
“…Raman spectroscopy is a non-invasive optical technique based on inelastic light scattering (Raman scattering), which changes the wavelength of the incident light depending on the structure of vibrational energy levels of tissue biomolecules such as lipids, proteins and nucleic acids [11,12,[52][53][54]. Raman spectroscopy has the ability to extract molecular-specific information of tissue constituents and their functional groups and molecular conformations based on the vibrational modes of tissue biomolecules [13,52,55].…”
Section: Introductionmentioning
confidence: 99%